2019
DOI: 10.3390/microorganisms7080272
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Non-O157 Escherichia coli from Cattle Faecal Samples in the North-West Province of South Africa

Abstract: Escherichia coli are commensal bacteria in the gastrointestinal tract of mammals, but some strains have acquired Shiga-toxins and can cause enterohemorrhagic diarrhoea and kidney failure in humans. Shiga-toxigenic E. coli (STEC) strains such as E. coli O157:H7 and some non-O157 strains also contain other virulence traits, some of which contribute to their ability to form biofilms. This study characterized non-O157 E. coli from South African cattle faecal samples for their virulence potential, antimicrobial res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
31
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 95 publications
(109 reference statements)
3
31
1
Order By: Relevance
“…In our previous study (Bumunang et al 2019), we detected biofilm forming genes via PCR and in silico whole genome sequencing of these isolates (supplementary Table S1 1 ). Molecular responses are known to play essential roles in biofilm-forming ability of non-O157 STEC in different environmental conditions (Farfan and Torres 2012).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In our previous study (Bumunang et al 2019), we detected biofilm forming genes via PCR and in silico whole genome sequencing of these isolates (supplementary Table S1 1 ). Molecular responses are known to play essential roles in biofilm-forming ability of non-O157 STEC in different environmental conditions (Farfan and Torres 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The STEC strains used in this study were selected among isolates from a previous study (Bumunang et al 2019) based on novelty (wzx-Onovel5:H19), multidrug resistance (streptomycin, tetracycline, ampicillin, chloramphenicol, trimethoprim-sulfamethoxazole, nalidixic acid, and norfloxacin; O154:H10), and ability to form intermediate to strong biofilm on polystyrene at 22 and 37°C (O26:H11, O116:H21, O129:H21, and O129:H23). These cultures were stored as glycerol stocks at -80°C.…”
Section: Bacterial Strainsmentioning
confidence: 99%
See 1 more Smart Citation
“…Different adhesive structures account for the capacity of STEC to bind to several surfaces, and autotransporters are important factors related to adherence and biofilm formation of non-O157 STEC [25]. A high occurrence of flu genes has been described among non-O157 STEC strains, but its presence was not statistically related to biofilm formation [26,27]. In this study, it was shown that the adherence of O105:H18 to rocket leaves significantly decreased when genes related to Sab were deleted, confirming previous observations on the participation of this AT in the adherence ability of non-O157 isolates [6].…”
Section: Discussionmentioning
confidence: 99%
“…Food products contaminated with Shiga toxin-producing Escherichia coli (STEC) have caused serious outbreaks in humans for decades [2][3][4]. For example, STEC serotype O113:H21, which has been associated with human illness [5,6] and O154:H10, which has the ability to colonize and form biofilms on food contact surfaces under different environmental conditions, also poses a health risk [7,8]. The persistence of STEC biofilms on food contact surfaces is a contributing factor to the contamination of food products [9,10].…”
Section: Introductionmentioning
confidence: 99%